Patient and hospital factors influencing discharge destination following hip fracture. (25th January 2021) - Ryder, Tayhla; Close, Jacqueline; Harris, Ian; Cameron, Ian D.; Seymour, Hannah; Armstrong, Elizabeth; Bell, Jack; Hurring, Sarah; Mitchell, Rebecca; ,
Abstract: Objective: To compare demographics, treatment and health outcomes for individuals hospitalised with a hip fracture and examine predictors of postacute discharge destination. Methods: A retrospective analysis of data from the Australian and New Zealand Hip Fracture Registry of individuals aged ≥50 years hospitalised with a hip fracture from 2015 to 2018 (n = 29 881). Multinominal logistic regression was used to examine factors associated with discharge destination for individuals from private residences. Results: Advancing age, impaired cognition, reduced walking ability and poorer pre‐operative health were predictors for discharge to residential aged care. The odds of discharge to a rehabilitation unit were higher for individuals with extracapsular fractures, treated at major trauma centres or at hospitals with home‐based rehabilitation. Individuals in rural areas had higher odds of discharge to another hospital or ward. Conclusion: In addition to well‐known demographics, injury and treatment factors, non‐clinical factors including geographic area of residence also affect discharge destination.